Effect of Presowing Treatments on Seed Germination and Growth Performance of 1-Year Lagerstroemia speciosa (L.) Pers Seedlings in Northeast India - Faisal Ismail Musa; Uttam Kumar Sahoo (The Scientific World Journal)
Lagerstroemia speciosa (L.) Pers (Lythraceae family), called pride of India, is an important ornamental and medicinal plant having a very high demand for its fruits. Six presowing treatments, that is, hot water, cold treatment, cow dung, H2SO4, gibberellic acid (GA3), and scarification, were used to evaluate the effect of treatments on seed germination, mean germination time, and germination energy and monitor the growth performance of seedling as well as seedling quality index of L. speciosa. Among the different treatments, hot water recorded the highest germination percentage (51.95%). However, minimum mean germination time was achieved by H2SO4 treatment (21.17 days). Additionally, a significant difference (p<0.05) was observed in germination rate among treatments and the number of seeds germinated per day among treatments. The mean seedling height of L. speciosa reached a maximum height of 104 cm and a diameter of 10.67 mm in 1 year. We found a strong relation between seedling height and soil temperature (r=0.56) and between seedling characteristics and biomass parameters, while there was a negative correlation with the total percentage of water content. The Dickson quality index of the seedlings was found to be 2.68. Our findings recommend hot water as the best treatment for ensuring quality seedlings, and seedlings of 1 year is sufficiently robust for large-scale afforestation and reforestation programs.